The Physical Generation is the Foundation of a Mature Army - Toshpolatov Abrorjon Mirhokimovich (Zien Journals, 2022)
This article will spring upcoming young generation to educate and them modern powerful army to the added contribution on research lit.
Keywords: healthy generation; maturity; army; physical perfection